Stability evaluation and heavy metal quantification of lotions from caprine milk, yogurt, and kefir - Fatchiyah Fatchiyah; Dewi Ratih Tirta Sari; Hazna Noor Meidinna; Nia Kurnianingsih; Ema Pristi Yunita; Sinta Murlistyarini (GarVal Editorial Ltda., 2023)
Context: Caprine milk has beneficial antioxidant and anti-inflammatory properties, thus the potential to be developed as a topical formulation against the skin-aging process. However, the influence of temperature during topical formulation storage from caprine milk must be explored. Aims: To analyze the physical stability and heavy metal contents of skin lotion from caprine milk, yogurt, and kefir. Methods: All lotions were storage at different conditions, such as 4°C, 25°C without light exposure (LE), 25°C with light exposure, and 33°C for 12 months. The characteristics of color, aroma, separation, viscosity, pH level, and heavy metals were determined periodically. Results: Yogurt lotions showed more maintained color, aroma, and separation under different storage conditions than milk and kefir lotions. The viscosity of all samples was relatively stable, with a minor reduction at 33°C of temperature storage. The longer duration of storage reduced the pH level for all lotions. Heavy metals were slightly detected in safe range values. Conclusions: This study concludes that the physical characteristics of lotions made from caprine milk, yogurt, and kefir were relatively stable during the different storage conditions, and these lotions are proposed as a safe topical formulation for skin application.